Acute effect of inhaled bradykinin on tracheobronchial clearance in normal humans. - Polosa, R (1992)
BACKGROUND: Bradykinin, a nonapeptide that contributes as a mediator to the pathogenesis of asthma, may affect lung mucociliary clearance, as it has been shown to be a potent secretagogue in canine airways and in human nasal mucosa in vivo. To evaluate this possibility the effect of inhaled bradykinin on mucociliary clearance has been studied in 10 healthy volunteers. METHODS: Subjects attended the laboratory on two occasions to take part in tracheobronchial clearance studies using a non-invasive radioisotopic technique. Inhalation of radioaerosol was followed 30 minutes later by inhalation of either bradykinin (8 mg/ml) or vehicle placebo in a randomised, double blind fashion. After each inhalation the number of coughs was recorded. Whole lung radioactivity was measured every half hour for six hours with two collimated scintillation counters, and a tracheobronchial clearance curve was plotted for each subject on each occasion. RESULTS: Mucociliary clearance, expressed as the area under the tracheobronchial radioaerosol retention curve calculated for the first six hours (AUC0-6h), was greater in nine out of 10 subjects after inhalation of bradykinin than after placebo. The median values (range) for AUC0-6h were significantly reduced from 126% (78-232%)/h with placebo to 87% (51-133%)/h with bradykinin. CONCLUSION: It is concluded that acute exposure to inhaled bradykinin accelerates tracheobronchial clearance in normal human airways.